The Worldwide Face of Elder Abuse - Teaster, Pamela B.; Anetzberger, Georgia J.; Podnieks, Elizabeth (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book provides a picture of the abuse of older adults, organized by World Health Region and locating the problem within an area's historic and present societal treatment of older persons. An actual and emblematic case study of the abuse of an older adult frames each chapter. Using the case study as a touchstone, each chapter guides the reader's understanding of elder abuse in the region or country through the use of empirical data and research on the problem, explaining its usefulness and limitations as well as guiding frameworks utilized to address the problem. The book highlights the efforts of leading figures in each area or region who are addressing the problem, explaining existing policies and future initiatives to address the abuse of older adults. By providing a holistic and person-centered picture of the issue and problem of elder abuse, based on actual experiences as well as national and international statistics and research and politics and policy, this book is an invaluable resource for students, academics, social service practitioners, health professionals, law enforcement, and policymakers around the world.
Chapter 1. Introduction to the Worldwide Face of Elder Abuse -- Chapter 2. Elder Abuse in Africa with a Special Focus on Nigeria -- Chapter 3. Between Treasuring and Mistreatment: Elder Abuse in the Eastern Mediterranean Region -- Chapter 4. Elder Abuse in India: Cultural Implications, Prevention Strategies, and Legislative Actions -- Chapter 5. Elder Abuse in the Context of Health Services in Mexico -- Chapter 6. Elder Abuse in the United States of America -- Chapter 7. Death by Neglect -- Chapter 8. From Protection to Safeguarding: Elder Abuse in England -- Chapter 9. The Face of Elder Abuse in Australia -- Chapter 10. A Tragic Case of Elder Abuse in Institutional Settings in Japan: What Can We Learn from this Case? -- Chapter 11. Concluding Thoughts -- Chapter 12. Elder Mistreatment, Evolving Possibilities.
Keywords: Age distribution (Demography).; Gerontology; Geriatrics; Social service -- Research; Aging Population; Gerontology; Geriatrics; Social Work Research